Teaching Quality in Geography: What Are We Trying to Achieve? - Lambert, David; Béneker, Tine; Bladh, Gabriel (Journal of Geography Education, 2024)
The fundamental argument in this contribution is that quality teaching is inseparable from the quality of curriculum thought, and this includes a crucial focus on the role of geography teachers as curriculum makers and knowledge workers. This thinking is explored from a Future 3 curriculum thinking perspective - to unlock the potential of the school subject - and a GeoCapabilities approach and practice. 'Knowledge working' with powerful disciplinary knowledge in relation to other ways of knowing, is seen as a bridge between the level of epistemological principle and classroom content selection. This opens the possibility for developing a practical theory of content for teachers to engage with.